In-situ bioremediation of soil pollution with electric heating temperature regulation Bio-Ventilation. Issue 4 (March 2019) - Yin, Xiaozhou; Sun, Xingbin; Yang, Yawei; Ding, Hanqing
Abstract: The relation between activity of soil indigenous microorganisms and temperature is an important research topic. The method of low rate flow nutrition and oxygen injection to a soil by an electrokinetic technique is studied to be used in aerobic polluted soil bioremediation treatments. The proper temperature nutrient solution and oxygen could be heated and poured into the polluted soil to promote the growth of indigenous bacteria in the soil and improve the efficiency of degrading inorganic pollutants. The present study was conducted to clarify oxygen levels and soil temperature influence on Bio-Ventilation bioremediation technology.